Implementing Prophetic Communication in the Leadership of HIQMA Student Organization at UIN Raden Intan Lampung - Meisya Solihhati; Faizal; Ade Nur Istiani (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
This study aims to analyze the implementation of prophetic communication in the leadership of the Student Activity Unit (UKM) HIQMA at UIN Raden Intan Lampung. Prophetic communication is based on three main pillars: humanization (amar ma’ruf), liberation (nahi munkar), and transcendence (tu’minuna billah). The research employed a descriptive qualitative method, using interviews, observations, and documentation as data collection techniques. The informants consisted of active administrators, alumni leaders, and members of UKM HIQMA selected through purposive sampling. The findings indicate that humanization is reflected in empathetic leadership, attention to members’ needs, and mentoring, which foster emotional closeness and organizational loyalty. Liberation is evident in the way leaders provide constructive criticism in a gentle and respectful manner, enabling members to grow with confidence. Transcendence appears through the integration of worship values such as prayer, dhikr, and Qur’anic recitation into organizational activities, which strengthens members’ spiritual motivation. Overall, prophetic leadership in UKM HIQMA successfully creates a humane, ethical, and spiritual organizational culture, proving the relevance of prophetic communication within student organizations.